The public land survey - Dorman, John Berthold (My University, 1896)
Introduction: In the treaty of peace signed by Great Britain and the United States in 1783 a great quantity of land besides that contained in the colonies was ceded to the United States. This together with that ceded by the individual colonies constituted a public domain of 404,955 square miles or 259,171,787 acres which at that time was simply wild undivided territory. In order that this great mass of land might be properly located and disposed of, Congress appointed a committee of five to draft some plans on which the work should be done; and accordingly on May 7, 1784 the committee submitted the following plan. The public land shall be divided in many ten mile squares, and these again into mile squares numbered from 1-100 beginning at the northwest and running from west to east and from east to west alternately throughout the square. On April 26, 1785 this was amended and submitted again; now requiring the country to be divided into townships seven miles square by lines funning due north and south and others east and west. These were to be again divided into one mile squares (640 acres) consisting of two sections of 320 acres each. This was again amended May 20, 1783 reducing the township to six miles square comprised of thirty six sections one mile square and numbered from one to thirty six beginning at the southeast corner and running from south to north in each tier of sections. It was under this system that the original surveys of the United States were made; the United States Geographer managing the work.
Citation: Dorman, John Berthold. The public land survey. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Usplss; Township and range; Surveying; United States; Geography; Theses; Manuscripts (documents)